Delivery of a macerated buffalo fetus by left-flank laparohysterotomy - HONPARKHE, M; GHUMAN, S P S; KUMAR, AJEET; SATHYA, A (The Indian Journal of Animal Reproduction, 2023)
The present case report describes the delivery of macerated fetus through left -flank laparohysterotomy in buffalo with uneventful recovery.